Integrating Remote Sensing with Ground-based Observations to Quantify the Effects of an Extreme Freeze Event on Black Mangroves (Avicennia germinans) at the Landscape Scale - Melinda Martinez; Michael J. Osland; James B. Grace; Nicholas M. Enwright; Camille L. Stagg; Simen Kaalstad; Gordon H. Anderson; Anna R. Armitage; Just Cebrian; Karen L. Cummins; Richard H. Day; Donna J. Devlin; et al. (Ecosystems, 2024)

Practical Guide to Measuring Wetland Carbon Pools and Fluxes - Sheel Bansal; Irena F. Creed; Brian A. Tangen; Scott D. Bridgham; Ankur R. Desai; Ken W. Krauss; Scott C. Neubauer; Gregory B. Noe; Donald O. Rosenberry; Carl Trettin; Kimberly P. Wickland; Scott T. Allen; et al. (Wetlands, 2023)
Wetlands cover a small portion of the world, but have disproportionate influence on global carbon (C) sequestration, carbon dioxide and methane emissions, and aquatic C fluxes. However, the underlying biogeochemical processes that affect wetland C pools and fluxes are complex and dynamic, making measurements of wetland C challenging. Over decades of research, many observational, experimental, and analytical approaches have been developed to understand and quantify pools and fluxes of wetland C. Sampling approaches range in their representation of wetland C from short to long timeframes and local to landscape spatial scales. This review summarizes common and cutting-edge methodological approaches for quantifying wetland C pools and fluxes. We first define each of the major C pools and fluxes and provide rationale for their importance to wetland C dynamics. For each approach, we clarify what component of wetland C is measured and its spatial and temporal representativeness and constraints. We describe practical considerations for each approach, such as where and when an approach is typically used, who can conduct the measurements (expertise, training requirements), and how approaches are conducted, including considerations on equipment complexity and costs. Finally, we review key covariates and ancillary measurements that enhance the interpretation of findings and facilitate model development. The protocols that we describe to measure soil, water, vegetation, and gases are also relevant for related disciplines such as ecology. Improved quality and consistency of data collection and reporting across studies will help reduce global uncertainties and develop management strategies to use wetlands as nature-based climate solutions.

Testing whether reducing brown trout biomass in peatland lakes increases macro-invertebrate biomass and invertivorous waterbird occurrence - Mark H. Hancock; Daniela Klein; Robert Hughes; Paul Stagg; Paul Byrne; Trevor D. Smith; Alison MacLennan; Paul P. J. Gaffney; Colin W. Bean (Aquatic Ecology, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Climate and plant controls on soil organic matter in coastal wetlands - Michael J. Osland; Christopher A. Gabler; James B. Grace; Richard H. Day; Meagan L. McCoy; Jennie L. McLeod; Andrew S. From; Nicholas M. Enwright; Laura C. Feher; Camille L. Stagg; Stephen B. Hartley (Global Change Biology, 2018)
Coastal wetlands are among the most productive and carbon‐rich ecosystems on Earth. Long‐term carbon storage in coastal wetlands occurs primarily belowground as soil organic matter (SOM). In addition to serving as a carbon sink, SOM influences wetland ecosystem structure, function, and stability. To anticipate and mitigate the effects of climate change, there is a need to advance understanding of environmental controls on wetland SOM. Here, we investigated the influence of four soil formation factors: climate, biota, parent materials, and topography. Along the northern Gulf of Mexico, we collected wetland plant and soil data across elevation and zonation gradients within 10 estuaries that span broad temperature and precipitation gradients. Our results highlight the importance of climate–plant controls and indicate that the influence of elevation is scale and location dependent. Coastal wetland plants are sensitive to climate change; small changes in temperature or precipitation can transform coastal wetland plant communities. Across the region, SOM was greatest in mangrove forests and in salt marshes dominated by graminoid plants. SOM was lower in salt flats that lacked vascular plants and in salt marshes dominated by succulent plants. We quantified strong relationships between precipitation, salinity, plant productivity, and SOM. Low precipitation leads to high salinity, which limits plant productivity and appears to constrain SOM accumulation. Our analyses use data from the Gulf of Mexico, but our results can be related to coastal wetlands across the globe and provide a foundation for predicting the ecological effects of future reductions in precipitation and freshwater availability. Coastal wetlands provide many ecosystem services that are SOM dependent and highly vulnerable to climate change. Collectively, our results indicate that future changes in SOM and plant productivity, regulated by cascading effects of precipitation on freshwater availability and salinity, could impact wetland stability and affect the supply of some wetland ecosystem services.

Causal mechanisms of soil organic matter decomposition: deconstructing salinity and flooding impacts in coastal wetlands - Camille L. Stagg; Donald R. Schoolmaster; Ken W. Krauss; Nicole Cormier; William H. Conner (Ecology, 2017)
Coastal wetlands significantly contribute to global carbon storage potential. Sea‐level rise and other climate‐change‐induced disturbances threaten coastal wetland sustainability and carbon storage capacity. It is critical that we understand the mechanisms controlling wetland carbon loss so that we can predict and manage these resources in anticipation of climate change. However, our current understanding of the mechanisms that control soil organic matter decomposition, in particular the impacts of elevated salinity, are limited, and literature reports are contradictory. In an attempt to improve our understanding of these complex processes, we measured root and rhizome decomposition and developed a causal model to identify and quantify the mechanisms that influence soil organic matter decomposition in coastal wetlands that are impacted by sea‐level rise. We identified three causal pathways: (1) a direct pathway representing the effects of flooding on soil moisture, (2) a direct pathway representing the effects of salinity on decomposer microbial communities and soil biogeochemistry, and (3) an indirect pathway representing the effects of salinity on litter quality through changes in plant community composition over time. We used this model to test the effects of alternate scenarios on the response of tidal freshwater forested wetlands and oligohaline marshes to short‐ and long‐term climate‐induced disturbances of flooding and salinity. In tidal freshwater forested wetlands, the model predicted less decomposition in response to drought, hurricane salinity pulsing, and long‐term sea‐level rise. In contrast, in the oligohaline marsh, the model predicted no change in response to drought and sea‐level rise, and increased decomposition following a hurricane salinity pulse. Our results show that it is critical to consider the temporal scale of disturbance and the magnitude of exposure when assessing the effects of salinity intrusion on carbon mineralization in coastal wetlands. Here, we identify three causal mechanisms that can reconcile disparities between long‐term and short‐term salinity impacts on organic matter decomposition.

Processes Contributing to Resilience of Coastal Wetlands to Sea-Level Rise - Camille L. Stagg; Ken W. Krauss; Donald R. Cahoon; Nicole Cormier; William H. Conner; Christopher M. Swarzenski (Ecosystems, 2016)

Emergence of undifferentiated colonies from mouse embryonic stem cells undergoing differentiation by retinoic acid treatment - Lioudmila V. Sharova; Alexei A. Sharov; Yulan Piao; Carole A. Stagg; Tomokazu Amano; Yong Qian; Dawood Dudekula; David Schlessinger; Minoru S. H. Ko (In Vitro Cellular & Developmental Biology - Animal, 2016)

Beyond just sea‐level rise: considering macroclimatic drivers within coastal wetland vulnerability assessments to climate change - Michael J. Osland; Nicholas M. Enwright; Richard H. Day; Christopher A. Gabler; Camille L. Stagg; James B. Grace (Global Change Biology, 2016)
Due to their position at the land‐sea interface, coastal wetlands are vulnerable to many aspects of climate change. However, climate change vulnerability assessments for coastal wetlands generally focus solely on sea‐level rise without considering the effects of other facets of climate change. Across the globe and in all ecosystems, macroclimatic drivers (e.g., temperature and rainfall regimes) greatly influence ecosystem structure and function. Macroclimatic drivers have been the focus of climate change‐related threat evaluations for terrestrial ecosystems, but largely ignored for coastal wetlands. In some coastal wetlands, changing macroclimatic conditions are expected to result in foundation plant species replacement, which would affect the supply of certain ecosystem goods and services and could affect ecosystem resilience. As examples, we highlight several ecological transition zones where small changes in macroclimatic conditions would result in comparatively large changes in coastal wetland ecosystem structure and function. Our intent in this communication is not to minimize the importance of sea‐level rise. Rather, our overarching aim is to illustrate the need to also consider macroclimatic drivers within vulnerability assessments for coastal wetlands.

A survey of wild marine fish identifies a potential origin of an outbreak of viral haemorrhagic septicaemia in wrasse, L abridae, used as cleaner fish on marine A tlantic salmon, S almo salar L ., farms - I S Wallace; K Donald; L A Munro; W Murray; C C Pert; H Stagg; M Hall; N Bain (Journal of Fish Diseases, 2015)
Viral haemorrhagic septicaemia virus ( VHSV ) was isolated from five species of wrasse ( L abridae) used as biological controls for parasitic sea lice predominantly, Lepeophtheirus salmonis ( K røyer, 1837), on marine A tlantic salmon, S almo salar L ., farms in S hetland. As part of the epidemiological investigation, 1400 wild marine fish were caught and screened in pools of 10 for VHSV using virus isolation. Eleven pools (8%) were confirmed VHSV positive from: grey gurnard, E utrigla gurnardus L .; A tlantic herring, C lupea harengus L .; N orway pout, T risopterus esmarkii ( N ilsson); plaice, P leuronectes platessa L .; sprat, S prattus sprattus L . and whiting, M erlangius merlangus L . The isolation of VHSV from grey gurnard is the first documented report in this species. Nucleic acid sequencing of the partial nucleocapsid ( N ) and glycoprotein ( G ) genes was carried out for viral characterization. Sequence analysis confirmed that all wild isolates were genotype III the same as the wrasse and there was a close genetic similarity between the isolates from wild fish and wrasse on the farms. Infection from these local wild marine fish is the most likely source of VHSV isolated from wrasse on the fish farms.

Sediment Accretion in Tidal Freshwater Forests and Oligohaline Marshes of the Waccamaw and Savannah Rivers, USA - Scott H. Ensign; Cliff R. Hupp; Gregory B. Noe; Ken W. Krauss; Camille L. Stagg (Estuaries and Coasts, 2014)

Vascular biomechanical properties in mice with smooth muscle specific deletion of Ndst1 - Neeta Adhikari; Marie Billaud; Marjorie Carlson; Spencer P. Lake; Kim Ramil C. Montaniel; Rod Staggs; Weihua Guan; Dinesha Walek; Snider Desir; Brant E. Isakson; Victor H. Barocas; Jennifer L. Hall (Molecular and Cellular Biochemistry, 2014)

Adaptive meshing in a mixed regime hydrologic simulation model - Jackie S. Pettway; Joseph H. Schmidt; Alan K. Stagg (Computational Geosciences, 2010)

Architecture of volcanic rifted margins: new insights from the Exmouth – Gascoyne margin, Western Australia - N. G. Direen; H. M. J. Stagg; P. A. Symonds; J. B. Colwell (Australian Journal of Earth Sciences, 2008)

Walking performance and its recovery in chronic stroke in relation to extent of lesion overlap with the descending motor tract - H. Dawes; C. Enzinger; H. Johansen-Berg; M. Bogdanovic; C. Guy; J. Collett; H. Izadi; C. Stagg; D. Wade; P. M. Matthews (Experimental Brain Research, 2008)

Geology of the Continental Margin of Enderby and Mac. Robertson Lands, East Antarctica: Insights from a Regional Data Set - H. M. J. Stagg; J. B. Colwel; N. G. Direen; P. E. O’Brien; G. Bernardel; I. Borissova; B. J. Brown; T. Ishirara (Marine Geophysical Research, 2004)